2021
DOI: 10.3390/coatings11101258
|View full text |Cite
|
Sign up to set email alerts
|

Durable Superhydrophobic Coating for Efficient Microplastic Removal

Abstract: The pollution caused by microplastics around the world is an increasingly significant issue that has to be tackled with different methods and technologies. Here, we report a straightforward and rapid process combining electrodeposition and electrophoresis to produce a durable superhydrophobic coating on an aluminum substrate (UNS A91070) that has a static contact angle (153°), sliding angle (1°), and contact angle hysteresis (1°). Field emission scanning electron microscopy and high-resolution transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Figure 2 presents different engineered adsorbents that are commonly in use for the adsorption of MPs from aqueous media [53]. It has been shown that removal efficiency of these adsorbents is between 25% for biochar [60] to ~ 100% for zinc laurate-TiO 2 particle coating [61]. It should be noted that the adsorption capacity of adsorbents is highly affected by the shape and size of MPs.…”
Section: Removal Methods Of Mps From Aqueous Environmentmentioning
confidence: 99%
“…Figure 2 presents different engineered adsorbents that are commonly in use for the adsorption of MPs from aqueous media [53]. It has been shown that removal efficiency of these adsorbents is between 25% for biochar [60] to ~ 100% for zinc laurate-TiO 2 particle coating [61]. It should be noted that the adsorption capacity of adsorbents is highly affected by the shape and size of MPs.…”
Section: Removal Methods Of Mps From Aqueous Environmentmentioning
confidence: 99%
“… 35 37 Recently, the ability of superhydrophobic materials to remove microplastics is attracting attention. A few articles show these innovative applications, 38 40 but the removal mechanism has to be exhaustively discussed considering the wetting properties from a chemical and physical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these surfaces can be used to separate oil from water mixtures as well as oil-in-water emulsions with extremely low oil contact angles (OCAs) close to 0°. Recently, the ability of superhydrophobic materials to remove microplastics is attracting attention. A few articles show these innovative applications, but the removal mechanism has to be exhaustively discussed considering the wetting properties from a chemical and physical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by natural lotus leaf, superhydrophobic surfaces show excellent water repellency with low wettability. Superhydrophobic surfaces are surfaces with a water contact angle of more than 150 • and a water sliding angle of less than 10 • , which are always constructed by combining appropriate micro/nano hierarchical structure with low surface energy materials [11][12][13][14]. Rough surface microstructure can be prepared by various methods, such as anodic oxidation, template, hydrothermal treatment, and sol-gel methods [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%